Strategi Pengembangan Sagu di Kabupaten Kepualauan Meranti - M Hamid (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2022)
The research objectives were to see (1) determine which sub-districts that have potential for sago development in Meranti Islands Regency, and (2) develop a sago crop development strategy to improve community welfare in Meranti Islands Regency. The research method used in this study is a mix method, which uses a quantitative approach with the Location Quotient (LQ) method to see which sub-districts are based on sago commodities in Meranti Islands Regency. In addition, using a qualitative approach with the SWOT analysis method to see the strengths, weakness, opportunities and threats in the development of sago plants in the region so that alternative strategies for the development of sago in the Meranti Islands Regency are prepared.The results of the LQ calculation show that the sago plantation commodity is the most superior commodity from other commodities, with an LQ value of 2.7294, meaning that this commodity is a regional superior commodity that can be developed and has great export potential outside the region. The results of the SWOT analysis show that sago development has internal strengths, but is faced with external threats that weaken competitiveness. The results of the space matrix model for sago development in Meranti Islands Regency are in the 5th quadrant For this reason, the sago development model in Meranti Islands Regency is focused on market penetration strategy or through identifying market absorption of the products produced. Market penetration is intended to prevent increasingly fierce business competition from sago products and their derivatives, namely by carrying out an aggressive marketing strategy. In addition, the product development strategy, namely the development of products that have a value proposition and increasing the uniqueness of the product can help the development of sago in Meranti Islands Regency in improving market performance and market expansion.